Socioeconomic inequalities in skilled birth attendance in Zimbabwe: a comparative analysis - Lukwa, Akim Tafadzwa (Health Economics Unit, 2021)
This dissertation assessed socioeconomic inequalities in skilled birth attendance in Zimbabwe. High maternal mortality in low-income countries is a cause of concern globally. Skilled birth attendance prevents a substantial number of maternal deaths and it is critical for ensuring overall maternal health. However, sub-Saharan Africa is characterized by challenges in accessing skilled birth attendance. The existence of health inequalities has been demonstrated when simple comparisons are made by residence (rural-urban), education and wealth (poorrich) in developing nations. The study used data from the Zimbabwe Demographic and Health Surveys (ZDHS) of 2010/11 and 2015. The analysis focused on women of child-bearing age (15-49 years). Skilled birth attendance was determined by women assisted by health personnel with midwife training. Health personnel was defined as a nurse, midwife or doctor. A binary logistic regression model was computed to understand the relationship between skilled birth attendance, demographic attributes and some explanatory variables. Standard concentration curves and Wagstaff normalized concentration indices were used to assess whether skilled birth attendance was dominant among the poor or rich in Zimbabwe. Overall skilled birth attendance prevalence increased for the periods under review. Regression results showed that antenatal care visits, residence status, place of delivery, women level of education, employment status and marital status are statistically significant predictors of skilled birth attendance. Wagstaff normalized concentration indices of aggregated use of skilled birth personnel reflected that wealthy women were more likely to receive skilled birth attendance. The concentration curves for aggregated skilled birth attendance showed minimal existence of health inequalities, as the concentration curves almost coincided with the line of equality. However, a disaggregated analysis by health personnel revealed the existence of health inequalities. In summary, minimal socioeconomic inequalities exist if skilled birth attendance aggregated, but when assessed by different health personnel categories, widening socioeconomic inequalities are observed.